Origin, Spread, Diagnostic Tests and Treatment for Covid-19 - M. Srinidhi (International Journal of Allied Medical Sciences and Clinical Research, 2020)
An acute respiratory disease, caused by a novel coronavirus (SARS-CoV-2, the coronavirus disease 2019 (COVID-19) has spread throughout China and received worldwide attention. On 30 January 2020, World Health Organization (WHO) officially declared the COVID-19 epidemic as a public health emergency of international concern. COVID-19 is the infectious disease caused by the most recently discovered coronavirus. This new virus and disease were unknown before the outbreak began in Wuhan, China, in December 2019. COVID-19 is now a pandemic affecting many countries globally. Most of these types of viruses have an origin in animals. The COVID-19 virus (also called SARS-CoV-2) is a new virus in humans. The most common symptoms of COVID-19 are fever, dry cough, and tiredness. Some patients may have aches and pains, nasal congestion, sore throat or diarrhea. These symptoms are usually mild and begin gradually. The disease spreads primarily from person to person through small droplets from the nose or mouth, which are expelled when a person with COVID-19 coughs, sneezes, or speaks. You are more likely to infect others in the early stages of the disease when you just have mild symptoms; therefore early self-isolation is very important. If you do not have symptoms, but have been exposed to an infected person, self-quarantine for 14 days. The goal of the self-quarantine is to prevent transmission. Since people who become ill with COVID-19 can infect people immediately self-quarantine can prevent some infections from happening. Studies have shown that the COVID-19 virus can survive for up to 72 hours on plastic and stainless steel, less than 4 hours on copper and less than 24 hours on cardboard. In some cases, patients were given an antiretroviral drug: lopinavir boosted with ritonavir (LPV/r). These studies were mostly carried out in HIV-negative individuals.